Sex‐specific body mass ageing trajectories in adult Asian elephants. (26th April 2022) - Lalande, Lucas D.; Lummaa, Virpi; Aung, Htoo H.; Htut, Win; Nyein, U. Kyaw; Berger, Vérane; Briga, Michael
Abstract: In species with marked sexual dimorphism, the classic prediction is that the sex which undergoes stronger intrasexual competition ages earlier or quicker. However, more recently, alternative hypotheses have been put forward, showing that this association can be disrupted. Here, we utilize a unique, longitudinal data set of a semi‐captive population of Asian elephants ( Elephas maximus ), a species with marked male‐biased intrasexual competition, with males being larger and having shorter lifespans, and investigate whether males show earlier and/or faster body mass ageing than females. We found evidence of sex‐specific body mass ageing trajectories: adult males gained weight up to the age of 48 years old, followed by a decrease in body mass until natural death. In contrast, adult females gained body mass with age until a body mass decline in the last year of life. Our study shows sex‐specific ageing patterns, with an earlier onset of body mass declines in males than females, which is consistent with the predictions of the classical theory of ageing. Abstract : Our study shows sex‐specific body mass ageing in Asian elephants. Males show an earlier onset of body mass ageing than females. Results are consistent with the sex‐specific predictions of the classical theory of ageing.